Basic Concepts in the Study of Procedural Law: About the Science of Process - Quiroga León, Anibal (1986)
The paper explores the foundations of procedural law, highlighting its relevance as a fundamental legal science for the social order. It begins with a critique of the doctrinal underdevelopment of procedural law in Peru, pointing out that procedural law has historically been considered secondary. He then presents several key concepts: traditional procedural law, which conceives it as a set of adjective rules subordinated to substantive law; modern procedural law, which frames it in a dialectical sphere with substantive law; and, finally, the post-publicist vision, which orients it towards social justice, understood as a fundamental right. Likewise, the author addresses concepts such as action, jurisdiction, competence and effective judicial protection, emphasizing the role of these in the impartial and peaceful resolution of conflicts, thus guaranteeing peace and justice in society. Finally, he emphasizes that the process is seen as a method that allows the adequate protection of fundamental rights, with both an individual and collective dimension.